PERKEMBANGAN REGULASI DAN PENGAWASAN FINANCIAL TECHNOLOGYDI INDONESIA - Njatrijani, Rinitami (Diponegoro Private Law Review, 2019)
ABSTRACT.  The growth of Fintech companies in Indonesia is very rapid, currently, there are 99 Fintech Companies in Indonesia. The Financial Sevices Authority (OJK) continues to encourage the development of information technology–based financial service provider company (Fintech). This paper discusses the regulation and supervision of fintech users in information technology-based lending and borrowing services. Legal protection for Fintech Indonesia Companies and Fintech Users and law inforecement. Regulating of technological innovation in finance must seek to balance compering objectives, especiallyfor innovation, financial stability, and customer protection. This is a particular challenge for regulators ten years after the global financial crisis prompted a massive focus on financial stability and enhanced consumer protection.